La función familiar y su relación con el intento autolítico en personas de 15 a 24 años de edad en la provincia de Zamora Chinchipe. - Mosquera González, Maritza Jhoanna (2017)
The autolytic attempt at the global, national and local level has increased considerably in the last years, especially in the ages between 15 and 24 years, reason why the present investigation has as main objective to evaluate the familiar functionality, sociodemographic and socioeconomic factors And to identify their relationship with the autolytic attempt in adolescents and young adults of the province of Zamora Chinchipe. It is an analytical study of cases and controls in which 93 people from 15 to 24 years of the province of Zamora Chinchipe participated, 31 people with antecedent of intent of suicide who represent the cases and 62 people without antecedent of autolítico attempt with similar characteristics, Which were chosen by stratified random sampling; The FFSIL test, the Beck suicide intentionality scale and the Plutchick suicide risk scale were applied, the analysis was performed in the SPSS software 16. The women constituted the highest percentage in cases and controls (55 and 58%); According to age the group aged 15 to 19 accounted for 61% in the cases and 66% in the controls, the mean of the cases was 19.26, whereas in the controls it was 19.39. According to the risk factors identified, 63.2% of the people who attempted to commit suicide came from dysfunctional families (Chi: 9.55; p: 0.002); they came from the rural area: 55.6% (Chi2: 4.96, p : 0.026); Have a 73.9% (Chi2: 22.64, p: 0.00), 66.7% have a family history of suicide (Chi2: 6.88, p: 0.009) and 55% have a level of education (Chi2: 5.383, p: 0.02), factors that are statistically significant. Therefore, it was possible to establish that if there is a statistically significant relationship between the presence of autolytic intent and family functionality in people aged 15 to 24 years in the province of Zamora Chinchipe; and being a preventable pathology, the characteristics of family functionality such as harmony, communication, adaptability, roles, cohesion and family permeability should be strengthened. Keywords: adolescents, young adults, risk factors, family function, suicide